1981
DOI: 10.1094/phyto-71-181
|View full text |Cite
|
Sign up to set email alerts
|

Adult Plant Resistance of Thatcher Wheat to Stem Rust

Abstract: No relationship was found between the independent Sr genes for seedling might be related to this Sr gene combination. The adult plant resistance of resistance and the adult plant resistance of Thatcher wheat, as measured by Thatcher was sensitive to inoculum density. Although this character had rust severity. Pyramids of seedling resistance genes Sr5, Srl2, Srl6, and been selected successfully under heavy inoculum density at the end of the SrTc did not improve resistance to stem rust. The performance of some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Since both parents showed susceptible infection types to these three races during seedling screening and were negative for the presence of Sr42 during marker screening, Sr42 may not be present in either parent. Another all-stage resistance gene present on 6DS, Sr5, is not effective against races in the Ug99 lineage ) and does not provide APR to stem rust when deployed singly, but it may be involved in APR when used with other genes (Nazareno and Roelfs 1981;Knott 2001). We do not have sufficient information to investigate the relationship between QSr.umn-6D and Sr5.…”
Section: Discussionmentioning
confidence: 94%
“…Since both parents showed susceptible infection types to these three races during seedling screening and were negative for the presence of Sr42 during marker screening, Sr42 may not be present in either parent. Another all-stage resistance gene present on 6DS, Sr5, is not effective against races in the Ug99 lineage ) and does not provide APR to stem rust when deployed singly, but it may be involved in APR when used with other genes (Nazareno and Roelfs 1981;Knott 2001). We do not have sufficient information to investigate the relationship between QSr.umn-6D and Sr5.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the present study indicate that seedling genes Sr12 and Sr16 may have contributed to Weld resistance. Nazareno and Roelfs (1981) studied segregating F 6 lines of Baart/Thatcher, and found no relationship between seedling resistance genes Sr9g, Sr5, and Sr16 and Weld resistance. They did, however, observe that lines with both Sr12 and SrTc had better Weld resistance than lines lacking both genes, although they concluded that the resistance must have come from a linked gene and not from either seedling gene per se, since there were susceptible lines that had both Sr12 and SrTc.…”
Section: Discussionmentioning
confidence: 99%
“…An additional seedling resistance gene temporarily designated SrTc has not been mapped, and other seedling resistances have not been fully described (Knott 2001;Nazareno and Roelfs 1981). The Sr genes confer resistance to some races of stem rust, but generally do not confer eVective resistance to the stem rust races currently found in the US (Kolmer et al 1991;Nazareno and Roelfs 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 'Thatcher' gives a 0; (fleck) infection type to race 56 at the seedling stage, but none of the genes it is known to carry condition better than an infection type 2 (Green and Dyck 1975;Nazareno and Roelfs 1981). It is not known whether the fleck infection type results from additive effects of two or more effective genes, or from modifying effects, or both.…”
Section: Introductionmentioning
confidence: 99%